STERILIS - THE MOST IMPORTANT MEDICAL, SOCIAL AND DEMOGRAPHIC PROBLEMS - Saparbayeva Nasiba Rakhimbayevna (Scholar Express Journals, 2022)
Preservation and restoration of reproductive health is the most important medical task of national importance. Therefore, modern diagnostics with subsequent treatment of infertility should be regarded as a reserve for the birth of desired children and an increase in the reproductive potential of the population. In order to systematize the most rational and reliable methods for examining infertile couples to clarify the causes of infertility and determine treatment tactics, a review of modern specialized literature was carried out. It was established that the mandatory methods for diagnosing infertility are a thorough history taking, examination, clinical, ultrasound, instrumental, radiological, pathohistological, genetic. It should be noted that infertility is a condition that characterizes a couple, and not a separate organism, so diagnostic algorithms should consider both partners.
Keywords: Infertility; Reproductive Dysfunction; Examinations; Folliculometry